Investigation of the temperature and DOD effect on the performance-degradation behavior of lithium–sulfur pouch cells during calendar aging. (15th February 2023) - Capkova, Dominika; Knap, Vaclav; Fedorkova, Andrea Strakova; Stroe, Daniel-Ioan
Abstract: High-energy density sulfur cathodes are one of the most promising possibilities to replace currently used intercalation cathodes in lithium-ion batteries in future applications. However, lithium–sulfur batteries are still the subject of research due to unsatisfactory capacity retention and cycle performance. The cause of insufficient properties is the shuttle effect of higher polysulfides which are formed in a high voltage plateau. In an effort to optimize storage conditions of lithium–sulfur (Li–S) batteries, long-term calendar aging tests at various temperatures and depth-of-discharge were performed on pre-commercial 3.4 Ah Li–S pouch cells. The decrease in performance over two years of calendar aging in five stationary conditions was analyzed using non-destructive electrochemical tests. The negative effect on Li–S cell performance was more pronounced for temperature than for depth-of-discharge. The analyses of self-discharge and shuttle current were performed and as expected, the highest values were measured in a fully charged state where higher polysulfides are present. Furthermore, internal resistance was analyzed where an increase of resistance was observed for a discharged state due to the formation of a passivation layer from discharge products (Li2 S2, Li2 S). To maximize the life of the Li–S battery, storage at high temperatures and in a fully charged state should be avoided. Graphical abstract: Highlights: Calendar aging tests of 3.4 Ah lithium–sulfur pouch cells have been investigated. Capacity loss is affected by temperature and depth-of-discharge during storage. Differential voltage analysis was used to study the calendar aging of Li–S batteries. Storage at low depth-of-discharge causes accelerated battery degradation. The increase in resistance was observed during storage in the discharged state.